Arab Americans in film : from Hollywood and Egyptian stereotypes to self-representation - Mahdi, Waleed F. (Critical Arab American studies., 2020)
""Arab Americans in Film" explores the representation of Arab Americans in Hollywood and Egyptian films that results in a unique and striking revelation of identity, belonging, and cultural citizenship"--